2004
DOI: 10.1021/jm030549j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure−Activity Relationships of Parasiticidal Thiosemicarbazone Cysteine Protease Inhibitors against Plasmodium falciparum, Trypanosoma brucei, and Trypanosoma cruzi

Abstract: We have synthesized a library of thiosemicarbazones and screened them against three parasitic cysteine proteases, cruzain, falcipain-2, and rhodesain, and against the respective parasite sources of these three proteases, Trypanosoma cruzi, Plasmodium falciparum, and Trypanosoma brucei. The screens identified compounds that were effective against the enzymes and the parasites but also some compounds that were parasiticidal despite a lack of activity against the proteases. Several compounds were effective in kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
153
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(161 citation statements)
references
References 19 publications
2
153
0
6
Order By: Relevance
“…The chelation of Fe from intracellular Fe pools results in the inhibition of RDR. The tridentate chelating thiosemicarbazones have been proposed to act by inhibiting RDR 13,[38][39][40] . Such compounds have also been proposed to act by inhibiting dihydrofolate reductase 41,42 .…”
Section: In Vitro Antileishmanial Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The chelation of Fe from intracellular Fe pools results in the inhibition of RDR. The tridentate chelating thiosemicarbazones have been proposed to act by inhibiting RDR 13,[38][39][40] . Such compounds have also been proposed to act by inhibiting dihydrofolate reductase 41,42 .…”
Section: In Vitro Antileishmanial Activitymentioning
confidence: 99%
“…Thiosemicarbazones are an important class of organic compounds, which possesses a number of medicinal properties, including antibacterial, antifungal, antiprotozoal, antitumoral, antiviral and more particularly, the antileishmanial activities [8][9][10][11][12][13][14][15][16][17][18][19][20][21] . Isatin-derived thiosemicarbazones have also been found to possess a variety of biological activities, such as antimicrobial, antineoplastic, antiplasmodial and antiviral [22][23][24][25][26][27][28][29][30][31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] In a previous study, the bis(thiosemicarbazone) complexes of copper have shown special promise as radiopharmaceuticals, as illustrated by the per fusion imaging agent. [5][6][7][8][9] Thiosemicarbazones have been reported to exhibit antituberculosis activity.…”
Section: Introductionmentioning
confidence: 99%
“…8) Thiourea derivatives have already been identified as potential antiprotozoal agents. Several works demonstrate their activity against Plasmodium falciparum, 11,16) Trichomonas vaginalis, 17) Trypanosoma cruzi 16,18) and Leishmania infantum, 18) and some examples of these compounds are given in Fig. 1.…”
mentioning
confidence: 99%